Assessment System for Assessing Knowledge Sharing Among Subject Experts in Secondary School - Elsawee, Amil Emhmed O (2011)
During the epoch of knowledge-based economy and knowledge management, teachers must learn in order to improve professional development. The success of knowledge management initiatives depends on knowledge sharing. The sharing of teaching-related knowledge may help teachers solve a variety of problems that they face, and the appropriate use of online knowledge-sharing activities is expected to assist teachers' knowledge sharing. Since studies related to educational knowledge sharing are rare, knowledge sharing behavior may be different between organization types. In order to promote knowledge sharing among subject experts within educational groups in secondary school; this study was implemented electronic assessment system to evaluate a knowledge sharing among teachers, which is helpful school organization's to develop knowledge and cultures.